2018
DOI: 10.1057/s41310-018-0036-0
|View full text |Cite
|
Sign up to set email alerts
|

Corporate reporting and disclosures in the emerging capital market of Kuwait: the perceptions of users and preparers

Abstract: The objective of this paper is to investigate the perceptions of users and preparers regarding financial disclosure practices in annual reports of Kuwaiti listed firms. To measure participants' views, a questionnaire survey was distributed in Kuwait between October and December 2012, to preparers (financial managers) and users (financial analysts) within Kuwaiti listed companies. The study compares between the perceptions of financial managers and financial analysts regarding to disclosing information in corpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…By contrast, other scholars (Vergoossen, 1993) revealed that the MR is a moderately important source of information for investors. In the emerging markets, several studies revealed that the MR has a moderate or slight level of usefulness for decision-making (Alzarouni et al, 2011;Biswas and Bala, 2016;Dawd et al, 2018;Mirshekary and Saudagaran, 2005;Stainbank and Peebles, 2006) while MEDAR 27,6 Alattar and Al-Khater (2008) reported that the MR is a relevant source of information for investment decisions in Qatar.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By contrast, other scholars (Vergoossen, 1993) revealed that the MR is a moderately important source of information for investors. In the emerging markets, several studies revealed that the MR has a moderate or slight level of usefulness for decision-making (Alzarouni et al, 2011;Biswas and Bala, 2016;Dawd et al, 2018;Mirshekary and Saudagaran, 2005;Stainbank and Peebles, 2006) while MEDAR 27,6 Alattar and Al-Khater (2008) reported that the MR is a relevant source of information for investment decisions in Qatar.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior literature indicated a strong support that individuals place more weight on evidence from a more reliable source when presented with conflicting evidence [31]. In auditing contexts, when presented with conflicting evidence, auditors are expected to place greater weight on audit evidence from a more reliable source.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unlike, MR corporate disclosure usefulness has a well-established literature in both western and LDCs. Usefulness of the annual report represent a mainstream in these studies (Allini et al, 2018;Biswas & Bala, 2016;Dawd et al, 2018;Lee & Tweedie, 1975), while some studies concentrated on the usefulness of specific items within the annual report (Biswas & Bala, 2016;Cohen et al, 2010;Dawd et al, 2018;Graham et al, 2002;Hassan & Power, 2009;Johansen & Plenborg, 2013;Khaled & Khaled, 2010;Orens & Lybaert, 2007;Stainbank & Peebles, 2006). As annual reporting disclosure is out of the scope of this research, what is important how they mentioned MR in their studies.…”
Section: Introductionmentioning
confidence: 98%
“…Stainbank and Peebles (2006), assures that users value information relating to forward-looking. While, Dawd et al (2018) reported the importance of liquidity, KPIs. Moreover, Alattar and Al-Khater (2007) concluded that MR represent a useful source of information for investors in Qatar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation